Peningkatan Kewaspadaan terhadap Hiperlipidemia Melalui Pemeriksaan Kadar Kolesterol pada Kelompok Lanjut Usia di Panti Werda Hana - Ruslim, Welly Hartono; Santoso, Alexander Halim; Kurniawan, Junius; Destra, Edwin; Setiawan, Fiona Valencia; Wijaya, Bryan Anna (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2024)
Hyperlipidemia, characterized by elevated levels of lipids such as cholesterol and triglycerides in the blood, significantly increases the risk of atherosclerosis, which causes cardiovascular disease, ischemic stroke, and peripheral arterial disease. Genetic tendencies and unhealthy lifestyles such as diet, smoking, and physical activity can cause this. This condition often does not cause symptoms, so it is necessary to carry out regular health checks. This activity uses the PDCA (Plan-Do-Check-Act) methodology to screen for hyperlipidemia in the elderly at the Hana Nursing Home, South Tangerang. This activity included 61 respondents, and 28 people (45.9%) experienced hypercholesterolemia. These results highlight the importance of routine lipid screening in identifying individuals at risk early, enabling timely intervention. This examination can significantly reduce morbidity and mortality, thereby improving overall quality of life.